HYDROCEPHALUS WITH VENTRICULOPERITONEAL SHUNT IN INFANTS: OUR EXPERIENCES AND CLINICAL OUTCOMES - Hristina Mandzukovska; Aspazija Sofijanova; Tamara Voinovska; Silvana Naunova Timovska; Mica Kimovska-Hristov; Besim Vejseli; Olivera Jordanova; Spasija Neskova-Jankovic (Macedonian Association of Anatomists, 2022)
AbstractHydrocephalus is a condition resulting from disorder in absorption and circulation of the cerebrospinal fluid (CSF). It leads toaprogressive ventricular dilatation and need of ventriculoperitoneal shunt (VP)placement. The aim of our study wasto present our experience withinfantswith hydrocephalus,ventriculoperitoneal shunt placement, and earlypostoperative follow-up.A retrospective study was conducted comprising infantswith hydrocephalus born between January 2019-January 2022with ventriculoperitoneal shunt placement performedatthe University Clinic for Neurosurgery in Skopje,Macedonia. Demographic and clinical characteristics, complications and the need for ventriculoperitoneal shunt were documented.Of twenty-three infantswith hydrocephalus,14 (60.8%) were preterm infants (median birth weight 2120g; mean gestational age 33.1weeks), 9(39.1%) were term infants(mean birth weight 3600g; mean gestational age 38.4 weeks). The etiology of hydrocephalus was:congenital hydrocephalusin 5infants(21.7%),prematurityin 6 infants(26.08%), spina bifida in 2 infants(8.7%),systemic infection in 4 infants(17.3%), and intraventricular hemorrhage in 6 infants(26.08%).Ventriculoperitoneal shunt was placed inall 23infants, at the mean age of 33.5(30-43) days.Postoperative complicationsas a result of ventriculoperitoneal shuntplacement were:ventriculitismanifested in3 preterm (13%) infants,of which 2(8.6%) died;fiveterm infants(21.7%) had postoperativeseizures, of which2 infants(8.6%) died. Nineteeninfants(82.6%) were discharged and transferredto the neonatology department. Ventriculoperitoneal shunt placementis atreatment of choice for infantswith hydrocephalus, although postoperative complications in preterm infantsincrease the percentageof morbidity and mortality.
Keywords: hydrocephalus; ventriculoperitoneal shunt; newborns; postoperative complications